2007
DOI: 10.2337/db07-1029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Implicating Eating as a Primary Driver for the Obesity Epidemic

Abstract: This article addresses the extent to which increases in energy intake as opposed to decreases in energy expenditure are driving the obesity epidemic. It argues that while both intake and expenditure are plausible and probable contributors, the fact that all intake is behavioral, whereas less than half of expenditure is behavioral, makes intake a conceptually more appealing primary cause. A review of per capita food disappearance trends over time and of trends in individual intakes is presented to support the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 18 publications
2
37
0
2
Order By: Relevance
“…These results are consistent with those from Harnack et al and Jeffery and Harnack, which showed that energy 2 0 0 0 2 0 0 1 1 9 9 8 1 9 9 9 1 9 9 6 1 9 9 7 1 9 9 4 1 9 9 5 1 9 9 3 1 9 9 2 2 0 0 3 2 0 0 1 1 9 9 7 1 9 9 9 1 9 9 3 1 9 9 5 1 9 8 9 1 9 9 1 1 9 8 7 1 9 8 5 1 9 9 1 1 9 9 0 1 9 8 9 1 9 8 8 1 9 8 7 1 9 8 6 1 9 8 (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) availability in the US food supply increased by 15 % between 1970 and 1994 (31) and by 22 % between 1982 and 2004 (32) . Results are also consistent with Bleich and colleagues, who have modelled the fraction of obesity due to energy in and energy out for a number of developed countries (10) .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those from Harnack et al and Jeffery and Harnack, which showed that energy 2 0 0 0 2 0 0 1 1 9 9 8 1 9 9 9 1 9 9 6 1 9 9 7 1 9 9 4 1 9 9 5 1 9 9 3 1 9 9 2 2 0 0 3 2 0 0 1 1 9 9 7 1 9 9 9 1 9 9 3 1 9 9 5 1 9 8 9 1 9 9 1 1 9 8 7 1 9 8 5 1 9 9 1 1 9 9 0 1 9 8 9 1 9 8 8 1 9 8 7 1 9 8 6 1 9 8 (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) availability in the US food supply increased by 15 % between 1970 and 1994 (31) and by 22 % between 1982 and 2004 (32) . Results are also consistent with Bleich and colleagues, who have modelled the fraction of obesity due to energy in and energy out for a number of developed countries (10) .…”
Section: Discussionmentioning
confidence: 99%
“…food deprivation; locomotor activity; diet-induced obesity THE RISING PREVALENCE OF OBESITY indicates that a sustained positive imbalance between energy intake and expenditure exists at the population level. However, it's unclear which factor, excessive intake or reduced energy expenditure, has contributed more to the obesity epidemic (19). Given the strong influence of genetics and environment on body weight gain, it's intriguing that spontaneous physical activity (SPA) has a strong familial and genetic component (65) and that lean adults and children display greater SPA than their obese counterparts (25,38).…”
mentioning
confidence: 99%
“…The reasons behind this epidemic are not clearly understood, however this metabolic disease can result from a complex interaction between many factors including genetic, physiological, behavioural and environmental influences. The rate at which this disease has increased suggests that environmental and behavioural factors such as increased consumption of high-fat and high-energy foods, coupled with reduced physical activity play a greater role than genetic causes [2][3][4] . It is therefore particularly relevant that recent epidemiological and animal studies have suggested that long-term health can be influenced by events in fetal and early infant phases of life.…”
Section: Introductionmentioning
confidence: 99%